The Economist pocket Asia - Andrews, John 1946- (Profile Books in association with The Economist, 2001)
Some two-thirds of the world's population lives in Asia, home to some to the most impressive economic growth in history. But it remains a generally poor region and a volatile one: prone to economic swings, political upsets and natural disasters.